2004
DOI: 10.1017/s1367943004001490
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural trait assessment as a release criterion: boldness predicts early death in a reintroduction programme of captive‐bred swift fox (Vulpes velox)

Abstract: Reintroduction of captive-bred animals is a key approach in conservation attempts for many endangered species, however, post-release survival is often low. Rearing conditions may be unlike those encountered upon release and the animals may not have had experiences necessary for survival in the wild. Animals may also habituate in captivity to stimuli that may pose a danger after release and/or there may be selection for behavioural traits, in particular reduced fearfulness, that may not be suited for the wild. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
190
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 28 publications
5
190
0
4
Order By: Relevance
“…In solitary animals, selection acts on individual phenotypes, e.g. high aggression in Ural owls [43] or low boldness in swift foxes [44]. Social species, however, are under multi-level selection [10].…”
Section: Discussionmentioning
confidence: 99%
“…In solitary animals, selection acts on individual phenotypes, e.g. high aggression in Ural owls [43] or low boldness in swift foxes [44]. Social species, however, are under multi-level selection [10].…”
Section: Discussionmentioning
confidence: 99%
“…Boldness scores, calculated according to BREMNER-HARRISON et al (2004), showed that, before antipredator training sessions, rheas were bolder than after. These results were more evident for rheas belonging to trained-group two, and less evident for trainedgroup one (which behave shyly before and after antipredator training), although this group displayed shy behaviours more intensively after the training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…According to this index, trained-group one showed more shy than trained-group two, avoiding to approach the novel objects; meanwhile, during antipredator training, it was trained-group one who behave boldly. In the calculation of the boldness score proposed by BREMNER-HARRISON et al (2004), fear behaviours are multiplied by zero, while bold behaviours are multiplied by two. Maybe these different weights given to the behaviour categories are responsible for this kind of antagonism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations